Role of Biosolids on Hydrophobic Properties of Sulfide Ores - Escudey-Castro, A; Escudey-Castro, A (2011)
The effect of biosolids on hydrophobic properties of sulfides ores was studied. The principal components of biosolids are humic substances, mainly humic acid, and phosphorus compounds. The feasibility of using biosolids as collector for copper sulfide ores (CSO) was performed through zetapotential measurements, FT-IR analysis and film flotation tests. Addition of different dosages of biosolids, a commercial humic acid (CHA), and an industrial collector makes the zeta potential of a copper sulfide ore more electronegative in the entire pH range studied. FT-IR spectra show that CHA can interact with mineral surfaces through outer-sphere linkages. CHA can adsorb physically on chalcopyrite and pyrite through hydrogen bonds or Van der Waals forces. Orthophosphate, however, adsorbs chemically on the surfaces of these mineralogical species through inner-sphere linkages. Therefore, biosolids that contains both humic acid and phosphorus compounds can interact with CSO surfaces through a complex mechanism involving both inner and outer-sphere linkages. Further, film flotation tests - in accordance with zeta potential results - show that biosolids adsorb on the surface of the sulfide ores investigated, changing their hydrophobicity. Biosolids show greater affinity for pyrite while commercial humic acid show similar behavior to industrial collectors. Therefore, both biosolids and humic acids can change the hydrophobic properties of sulfide ores and can be used as collectors in froth flotation processes. Further research will be needed in order to scale-up laboratory results to industrial mineral operations. © 2011 Elsevier B.V. All rights reserved.